2017
DOI: 10.1038/s41598-017-15870-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Myocardial Infarction with Gene-modified Mesenchymal Stem Cells in a Small Molecular Hydrogel

Abstract: The effect of transplanted rat mesenchymal stem cells (MSCs) can be reduced by extracellular microenvironment in myocardial infarction (MI). We tested a novel small-molecular hydrogel (SMH) on whether it could provide a scaffold for hepatocyte growth factor (HGF)-modified MSCs and alleviate ventricular remodeling while preserving cardiac function after MI. Overexpression of HGF in MSCs increased Bcl-2 and reduced Bax and caspase-3 levels in response to hypoxia in vitro. Immunocytochemistry demonstrated that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Hydrogels injected directly into damaged cardiac tissue can serve as a potential delivery vehicle for cells, growth factors, and therapeutic peptides or drugs, etc . Hydrogels may also be used to support various gene delivery systems, including viral and non‐viral methods, enabling controlled delivery to the desired site and efficient localized therapy . Such deliverables could be specifically sequestered to the target tissue, reducing nonspecific spreading to other nearby tissues.…”
Section: Overview Of Injectable Hydrogels For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Hydrogels injected directly into damaged cardiac tissue can serve as a potential delivery vehicle for cells, growth factors, and therapeutic peptides or drugs, etc . Hydrogels may also be used to support various gene delivery systems, including viral and non‐viral methods, enabling controlled delivery to the desired site and efficient localized therapy . Such deliverables could be specifically sequestered to the target tissue, reducing nonspecific spreading to other nearby tissues.…”
Section: Overview Of Injectable Hydrogels For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…The anti‐apoptotic effect of BMSCs was also demonstrated in several tissues; in ischaemic myocardial cells, damaged liver cells and neural cells, BMSCs helped to reduce apoptosis and promote matrix remodelling, and the mechanisms underlying this result were thought to be cytokines produced by the paracrine effect of the BMSCs . Differentiation was also found to be another important aspect, as the transplanted BMSCs expressed several functional cell markers; however, the functions of the differentiated cells remain controversial . Recently, studies have shown that BMSCs can regulate autophagy …”
Section: Discussionmentioning
confidence: 99%
“…however, the functions of the differentiated cells remain controversial. [35][36][37] Recently, studies have shown that BMSCs can regulate autophagy. 15,16 Autophagy, one of the important mechanisms underlying survival and cellular homoeostasis maintenance, functions by decomposing cellular composition under stresses, such as starvation and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and colleagues induced overexpression of HGF in MSCs following administration into a mouse model of MI [489]. In addition to increased survival of modified MSCs probably induced by increased B cell lymphoma (Bcl)-2 and reduced Bax and caspase-3 levels [490], the authors detected an enhancement of angiogenesis, LVEF and proliferation capacity of resident cardiomyocytes upon SC treatment [489]. Moreover, overexpression of anti-apoptotic factors like Bcl-xL and Bcl-2 was found to positively influence the viability and therapeutic efficiency of applied SCs [491,492].…”
Section: Genetic Sc Modificationsmentioning
confidence: 99%